PENGARUH RASIO KEUANGAN TERHADAP RETURN SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Abdullah Abdullah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
This study aims to determine the effect of Earnings per share, price earnings ratio, and price to book value of stock returns on manufacturing companies listed on the Indonesia Stock Exchange. The sample of research used as many as 16 companies from 147 population in manufacturing sector. The type of data used is secondary data of each manufacturing company listed on the Indonesia Stock Exchange for 3 years is 2014,2015 and 2016. Sampling is done by purposive sampling. Data analysis using multiple regression analysis tool that preceded by classical assumption test consist of normality test, multicolinearity test, and heteroscedasticity test. Hypothesis testing is done by using t test, f test and coefficient of determination (R2). The results showed that the variable Earnings per share (EPS) and price earnings ratio (PER) have a significant positive effect on stock returns by partial. While the variable price to book value (PBV) has an insignificant positive effect on stock returns of manufacturing companies by partial. variable Earnings per share (EPS), price earnings ratio (PER) and Price to book value have a effect on stock returns of manufacturing companies by simultaneous. variable Earnings per share (EPS) is the dominant factor against effect on stock returns.